Core Java - Horstmann, Cay S., 1959- (Boston : Pearson, 2019)
"Core Java" has long been recognized as the leading, no-nonsense tutorial and reference for experienced programmers who want to write robust Java code for real-world applications. Now, Core Java, Volume I Fundamentals, Tenth Edition, has been extensively updated to reflect the most eagerly awaited and innovative version of Java in years: Java SE 8. Rewritten and reorganized to illuminate new Java SE 8 features, idioms, and best practices, it contains hundreds of example programs all carefully crafted for easy understanding and practical applicability. Writing for serious programmers solving real-world problems, Cay Horstmann helps you achieve a deep understanding of the Java language and library. In this first volume of the two-volume work, Horstmann focuses on fundamental language concepts and the foundations of modern user interface programming. You ll find in-depth coverage of topics ranging from Java object-oriented programming to generics, collections, lambda expressions, Swing UI design, and the latest approaches to concurrency and functional programming.--
V. 1. Fundamentals -- Chapter 1: An Introduction to Java -- Chapter 2: The Java Programming Environment -- Chapter 3: Fundamental Programming Structures in Java -- Chapter 4: Objects and Classes -- Chapter 5: Inheritance -- Chapter 6: Interfaces, Lambda Expressions, and Inner Classes -- Chapter 7: Exceptions, Assertions, and Logging -- Chapter 8: Generic Programming -- Chapter 9: Collections -- Chapter 10: Graphical User Interface Programming -- Chapter 11: User Interface Components with Swing -- Chapter 12: Concurrency. V. 2. Advanced features-- Chapter 1: Streams -- Chapter 2: Input and output -- Chapter 3: XML --Chapter 4: Networking -- Chapter 5: Database programming -- Chapter 6: The date and time API --Chapter 7: Internationalization -- Chapter 8: Scripting, compiling, and annotation processing -- Chapter 9: The Java platform module system -- Chapter 10: Security -- Chapter 11: Advanced swing and graphics -- Chapter 12: Native methods.
Includes index.
CSE
Keywords: Java (Computer program language).; Java (Computer program language); Computer science